The development of homogeneity psycho cognition learning strategy in physical education learning - Albertus Fenanlampir; Marleny Leasa; John Rafafy Batlolona (International Journal of Evaluation and Research in Education (IJERE), 2021)
Many future studies have been developed by scientists today in the form of methods, models, strategies, and techniques in improving student learning outcomes that are oriented to psychology and the development of students' intelligence. One of the latest innovations in learning offered in this study is the homogeneity psycho cognition (HPC) strategy. The research objective was to develop the latest learning strategies in physical education, sports, and health learning. This development research uses a 4D model consisting of four stages: define, design, develop, and disseminate to produce products in the form of an HPC learning strategy. This study involved 115 elementary school students in several sample schools in Ambon City as participants. This study found that the HPC learning strategy had been developed following the relevant development directions and procedures. The validation of the HPC strategy by experts indicates that the HPC strategy is feasible to implement with due regard to minor revisions. The results of small and medium-scale trials show that the HPC strategy can improve student learning outcomes.